Silicon-Organic Hybrid Modulators Based on a Coupled One-Dimensional Photonic Crystal Slot Resonator Waveguide - Li, Yanmei; Yan, Likang; Feng, Yang; Wang, Jinzhao; Li, Rui; Yao, Weiming; Yao, Yong; Xu, Xiaochuan (IEEE photonics journal, 2025)
High-speed and energy-efficient optical interconnects critically rely on electro-optical (EO) modulators, whose performance metrics struggle to meet the exponentially increasing demands of the near future. Silicon-organic hybrid (SOH) modulators present a promising solution due to the favorable electro-optic coefficients and fast response times of EO organic materials. However, the waveguide's nature limits the effective interaction between photons and EO materials. Although this interaction can be enhanced by utilizing advanced structures such as slot waveguides and slow-light techniques, new challenges arise, including strong dispersion that compromises bandwidth. In this paper, we propose a novel low-dispersion, slow-light waveguide structure based on a coupled one-dimensional photonic crystal slot resonator waveguide (coupled 1D PC SROW). By cascading multiple coupled resonators, the structure creates a low-dispersion, slow-light region within the photonic bandgap. Combining the strong optical field confinement of the slot with the slow-light enhancement in the time domain, modulation efficiency, quantified by V π L , can be significantly improved. As an example, we demonstrate that a V π L of 0.57 Vmm can be achieved for a low-dispersion wavelength range of 2.55 nm. The improvement in modulation efficiency allows for a reduction in the phase shifter length to 119 μm, overcoming the bandwidth limitations imposed by spatial walk-off between the electrical and optical waves and enabling a bandwidth of 108 GHz, a value challenging for conventional approaches. This study presents a viable alternative for realizing compact, ultra-broadband, and energy-efficient optical modulators.